(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
Fuzzy soft set theory is becoming more and more important for coming up with coherent and logical answers to numerous real-world issues that are riddled with uncertainty, imprecision, and vagueness. The intuitionistic fuzzy soft set was investigated theoretically later on. Wherever uncertainty resulting from ambiguity manifests in more sophisticated ways, the combination of intuitionistic fuzzy set and intuitionistic fuzzy soft set is more efficient from an implementational standpoint. In this paper, the motivation of our work is to establish a new methodology to select an object from an inexact multiobserver data with the idea of intuitionistic fuzzy soft set theory. Our methodology includes an algorithm based on “and”, “or” operation, max, min comparison data and comparison table. J. Bangladesh Acad. Sci. 47(1); 109-117: June 2023